2020
DOI: 10.1111/1460-6984.12555
|View full text |Cite
|
Sign up to set email alerts
|

A survey of cognitive–communication difficulties following TBI: are families receiving the training and support they need?

Abstract: Background Whilst research into the wide‐ranging needs of family members following traumatic brain injury (TBI) is well established, investigation into the specific needs of families in relation to supporting cognitive–communication difficulties, relationships and social participation is limited. Aims To identify the family needs for cognitive‐communication difficulties following TBI and to explore whether current services are meeting these needs. Methods & Procedures Following a successful pilot, family membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Participants in the 36 months + focus groups continued to express concern about the same CCD changes that were identified by participants in the 0-12 months and 12-36 months groups. This lends support to the findings that CCD difficulties persist over time (15,16,24,27,65) and reinforces the need for further longitudinal research and clinical support over this trajectory (25).…”
Section: Relationshipssupporting
confidence: 77%
See 1 more Smart Citation
“…Participants in the 36 months + focus groups continued to express concern about the same CCD changes that were identified by participants in the 0-12 months and 12-36 months groups. This lends support to the findings that CCD difficulties persist over time (15,16,24,27,65) and reinforces the need for further longitudinal research and clinical support over this trajectory (25).…”
Section: Relationshipssupporting
confidence: 77%
“…Family caregivers report less stress at social events and improved confidence in supporting the person following TBI in conversations following CPT interventions (64). Few studies have explored how family members experience and manage the consequences of CCD over the longer term, however, and a recent survey identified that families experience high levels of unmet need for CCD over this trajectory (65).…”
Section: Cognitive-communication Difficulties (Ccd) Resulting From Di...mentioning
confidence: 99%
“…Also, the need for speech-language pathology referral may be hidden in subpopulations where ABI-related cognitive-communication difficulties are superseded or obscured by other treatment priorities such as for those with spinal cord injury (Gordan et al, 2012), encephalitis and Lyme disease (Langenbahn et al, 2013), or COVID-19 influenza (Ramage, 2020). When cognitive-communication difficulties appear at later stages such as return to work or school, many are unable to find their way to speechlanguage pathology services due to unclear systems or lack of knowledge of rehabilitation services (Douglas et al, 2016;Gagnon et al, 2008;Grayson et al, 2020;Kennedy et al, 2008;Tran et al, 2018). In all of these instances, when the individual is outside of a care pathway leading to speechlanguage pathology, when referral sources are less knowledgeable or less inclined, or where funding sources are untrained or uncompelled to assist, the responsibility falls to the individual or family to describe communication challenges and self-advocate by using the very communication skills that are impaired.…”
mentioning
confidence: 99%
“…These consultations led us to shape the clinical recommendations in the CCEAS-Map to include provision of 'tailored' approaches to education and support, 'written' information, 'ongoing access' to information as needs and awareness change, and to provide 'options' adapted to their needs and preferences. Furthermore, based on our consultations and reviews of family education (Grayson et al, 2020), and communication partner training (Behn et al, 2021;Wiseman-Hakes et al, 2020), we decided to emphasize the overarching principles of 'person-centred', 'collaboration', 'contextual' and 'life participation' approaches to intervention. We, therefore, changed the title of the CCEAS-Map Education and Counselling section to Overall Principles and Approaches to Intervention to encapsulate these principles.…”
Section: Education Counselling and Therapeutic Relationshipmentioning
confidence: 99%